World on the edge : - Brown, Lester R. (W. W. Norton, 2011)
We are in a race between political and natural tipping points. Can we close coal-fired power plants fast enough to save the Greenland ice sheet and avoid catastrophic sea level rise? Can we raise water productivity fast enough to halt the depletion of aquifers and avoid water-driven food shortages? Can we cope with peak water and peak oil at the same time? These are some of the issues Lester R. Brown skillfully distills in World on the Edge. Bringing decades of research and analysis into play, he provides the responses needed to reclaim our future.